Stacking Interactions: A Supramolecular Approach to Upgrade Weak Halogen Bond Donors; Chemistry - A European Journal; Vol. 28, iss. 70 - Baykov S. V. Sergey Valentinovich; Ivanov D. M. Daniil Mikhaylovich; Kasatkina S. O. Svetlana Olegovna; Galmes B. Bartomeu; Frontera A. Antonio; Resnati D. P. Dzhuzeppe Paolo; Kukushkin A. Yu. Vadim Yurjevich (2022, 2022)
Title screen